Sustainable analytical approaches for microplastics in wastewater, sludge, and landfills: Challenges, fate, and green chemistry perspectives - Maryam Mallek; Damia Barcelo (Advances in Sample Preparation)
The effects of microplastics (MPs) in wastewater, sludge, and landfills are analyzed and discussed, focusing on their pathways into the environment. The application of sludge as a soil amendment and the reuse of treated wastewater in agriculture have been further proven to contribute to the introduction of MPs into terrestrial ecosystems. MPs present a capacity to accumulate in plants together with co-contaminants such as heavy metals and pharmaceuticals, posing additional risks to food safety and soil quality. This review underscores the need to align analytical practices with sustainability by adopting environmentally friendly methods. A critical discussion is presented on the analysis of MPs, encompassing an in-depth examination of analytical methodologies, challenges in sample preparation, and potential solutions. Techniques such as Fourier Transform Infrared Spectroscopy (FTIR), Raman Spectroscopy, and Pyrolysis-GC–MS (Py-GC–MS) are highlighted for their effectiveness in MP identification, combined with treatment approaches like density separation, enzymatic digestion, and oxidation. MPs appear in various forms, including synthetic fibers, microbeads, and fragmented particles, with their distribution being influenced by polymer types. Low-density polymers like polyethylene (PE) and polypropylene (PP) tend to remain in the water phase, whereas high-density polymers such as polyester (PES/PEST) and polytetrafluoroethylene (PTFE) accumulate in solid matrices like sludge and sediments. Inconsistencies in measurement units are a significant issue in microplastic analysis. Concentrations are typically reported as items per liter (for water) or items per kilogram (for soil), However, mass-based units such as µg/L are rarely employed, complicating data comparison. Another essential component is the determination of MP size, which is largely dependent on analytical equipment detection limits and resolution. Most studies focus on MPs ranging from 20–50 µm to a few millimeters, with limited research addressing MPs smaller than 0.1 µm, known as nanoplastics (NPs). Lastly, sustainable management approaches for addressing the worldwide problem of plastic pollution will be presented.